Effect of different levels of water on qualitative characteristics of Lassi prepared from reconstituted milk - Zohra, FT; Islam, MN; Siddiki, MSR; Habib, MR; Afrin, S (Bangladesh Journal of Animal Science, 2017)
Present research work was designed to develop lassi from reconstituted milk using different levels of water. For this purpose, dahi was prepared from reconstituted milk using traditional starter culture. Four different types of lassi were prepared by mixing dahi with 15, 20, 25 and 30% water and sugar level in all samples were 20%. The quality of lassi from reconstituted milk was evaluated by a panel of expert judges by different physical tests using a score card. There was non-significant difference (p>0.05) among the overall physical score of lassi samples. Result revealed that the highest overall score was recorded in 20% added water lassi sample whereas the lowest score was found in 30% added water lassi sample. In chemical analysis, significant differences (p<0.01) existed among the total solids, carbohydrate, fat, protein, moisture content and pH value but non-significant differences (p>0.05) were seen for ash content and acidity percentage. The total bacteria, coliform, yeast and mold in all samples did not exceed the legal standard. From the findings of this study, it might be concluded that lassi could be prepared successfully from reconstituted and mixing reconstituted milk dahi with 20% water along with 20% sugar will produce better quality lassi. Bang. J. Anim. Sci. 2016. 45 (3): 46-51